2002
DOI: 10.1046/j.1365-2133.2002.04807.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous embolization of cardiac myxoma

Abstract: Atrial myxoma is the most common primary tumour of the heart. Skin manifestations in patients with a cardiac myxoma are frequent and may be due to cutaneous emboli, or may be specific findings as part of more complex syndromes. We present a 33-year-old-man with a history of episodes of pain in both legs and an ischaemic neurological event, who also had episodes of acral papular erythematous lesions on the legs and feet including the soles. The histological finding of dermal vessels occluded by a myxomatous mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The demonstration of a myxomatous embolus in a skin biopsy is not always possible, and it often requires the examination of multiple sections or multiple biopsies . A cutaneous embolism from an atrial myxoma has been reported on eight occasions previously, however, most of these cases also presented with neurological symptoms, which facilitated the diagnosis. In addition, cases presenting with isolated skin lesions were diagnosed only after a histopathological correlation of biopsy specimens …”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of a myxomatous embolus in a skin biopsy is not always possible, and it often requires the examination of multiple sections or multiple biopsies . A cutaneous embolism from an atrial myxoma has been reported on eight occasions previously, however, most of these cases also presented with neurological symptoms, which facilitated the diagnosis. In addition, cases presenting with isolated skin lesions were diagnosed only after a histopathological correlation of biopsy specimens …”
Section: Discussionmentioning
confidence: 99%
“…Skin manifestations in patients with a left atrial myxoma are frequent, usually on acral sites, and accompanied by cardiopulmonary symptoms. [7]…”
mentioning
confidence: 99%
“…However, in cases of massive embolism, the cardiac tumor can disappear 7,15,16 . Occasionally, the existence of a cardiac myxoma has been anticipated following the histological examination of an embolus 6,7 or skin biopsy 17–22 …”
Section: Discussionmentioning
confidence: 99%